Development of a Miniature Recorder for Drilling Motors. (November 2020) - Li, Fei; Song, Haolan
Abstract: A recorder is designed to record the vibration data of the drilling motor for health assessment of the motor to improve the drilling efficiency. It is installed in the rotor catch of the drilling motor without increasing the length of the bottom hole assembly(BHA). The recorder is equipped with two triaxial vibration accelerometers with different ranges, a rate gyroscope, a temperature sensor, and an integrated circuit (IC) for timestamps. The recorder can measure and record the vibration data of the entire operation cycle of the ground transportation, rig-side handling and downhole operations of the motor. Vibration recorder does not require any configuration or intervention at rig sides so that it can be easily deployed to motor operations. The Python-based data analysis software was developed for the miniature vibration recorder. The analyzer can make statistics on the recorded data and display it with time plots and histogram. The vibration recorders provided adequate information of a drilling motor to maintenance shops and operator. These statistical data and charts can help users understand transportation, rig-side handling and downhole drilling.